Vibration training: Could it enhance the strength, power, or speed of athletes? - Wilcock, I. M.; Whatman, C.; Harris, N.; Keogh, J. W. L. (The Journal of Strength and Conditioning Research, 2009)
The aim of this literature review was to determine whether vibration training could produce chronic improvements in the physical performance of trained athletes. Although the main objective was to analyze any performance benefits, a brief review of possible mechanisms linked to performance enhancement is also included. Vibration causes an increase in the g-forces acting on the muscles, increasing the loading parameters of any exercise. Increased loading should aid muscle hypertrophy, and some authors have suggested that vibration may enhance neuromuscular potentiation. Considering the 6 studies on trained athletes, there does seem to be some evidence to suggest that vibration may provide a small benefit to maximal strength (1-repetition maximum) and power (countermovement jumps) of trained athletes. Speed does not seem to be enhanced by vibration training. There is a lack of evidence to support the theory that long-term vibration training increases neuromuscular potentiation in trained athletes. What mechanism(s) could be responsible for possible strength and power enhancement is unclear. Because whole-body vibration does not seem to be detrimental to performance when used in a controlled manner, it could provide an additional training stimulus for athletes. However, further research is required to determine optimum vibration training protocols and to clarify whether vibration training produces performance benefits greater than those of traditional training methods.